Triple Hypoxia Syndrome - Zubieta-Castillo, G.; Zubieta-Calleja, G. (Acta Andina, 2025)
Many patients with excessive erythrocytosis (EE), with hematocrit greater than 55%, but lower than 70%, apparently are normal. They work. play soccer, develop intellectual activities and frequently perform better than sedentary normal people (3500 m). They request medical attention, only when they present symptoms similar to those of acute mountain sickness (AMS), such as: headache, dyspnea, nausea, lassitude and indigestion. Without going higher they have been said to experience "sorojchi (AMS) in bed". They show extreme hypoxia with an oxygen arterial tension (PaO2) near 20 mmHg, with or withouthypercapnia and a normal or acidotic pH. We have previously named this complication of EE, as the triple hypoxia syndrome (THS). It is due to: [1] Normal high altitude adaptation to hypoxia, [2] EE hypoxia (CMS) and [3] acute hypoxia that can be reversed by oxygen. The THS is similar to "surviving" on the summit of Mount Everest. It may be caused by viral infections ( flu ) or some other acute respiratory disease, with malaise that lasts several days without treatment and trypically is reversed by 24 hours of oxygen to PaO2 baseline values of their chronic condition with EE. The diagnosis is important, since the THS is an acute transitory condition, that when not recognized and treated with oxygen can possibly lead to cardiac, pulmonary or cerebral complications.